Polyphenols from Alcoholic Apple Cider Are Absorbed, Metabolized and Excreted by Humans - DuPont, M. Susan; Bennett, Richard N.; Mellon, Fred A.; Williamson, Gary (The Journal of nutrition, 2002)
We determined the uptake and excretion of low doses of polyphenols in six subjects who each consumed 1.1 L of an alcoholic cider beverage. Over a 24-h period, no phloretin was detected in plasma (detection limit = 0.036 μmol/L), but 21 ± 5% of the dose (4.8 mg) was excreted in the urine. In contrast, from a low dose of 1.6-mg quercetin equivalents, no quercetin was found in urine or plasma, but 3′-methyl quercetin was detected in plasma [Cmax (maximum concentration) = 0.14 ± 0.19 μmol/L; range: 0 to 0.44 μmol/L]. No flavanol monomers (dose of free (+)-catechin and (−)-epicatechin = 3.5 mg) were detected in urine or plasma (detection limit: 0.01 μmol/L). Caffeic acid (total dose including esters = 11 mg) was detected only in plasma within 2 h, with Cmax = 0.43 ± 0.3 μmol/L (range: 0.18 to 0.84 μmol/L). An almost 3-fold increase in hippuric acid was detected in 24-h urine (74 ± 29 μmol/L; range: 38–116 μmol/L), compared with a prestudy value of 19 ± 9 μmol/L. These data show that polyphenols are taken up from cider, that phloretin is excreted in the urine and suggest that low doses of quercetin are extensively methylated in humans.